Rumah Adat Bandung Rangki di Desa Pedawa, Kecamatan Banjar, Buleleng - Trisna Damayanthi, Ni Komang; Suarsana, I Nyoman (Humanis; Vol 24 No 1 (2020), 2020)
Traditional house is a traditional building that has a function not only as place for living but also as place for holding traditional activities that have been carried out for generations. Pedawa village which is located in Buleleng regency has a traditional house named Bandung Rangki which is a single building that owned by individuals. This study is intended to find out the form of bandung rangki, and the change of bandung rangki which is located in Pedawa village, Banjar district, Buleleng. The result of this study is expected to be useful for the development of anthropology especially about traditional architecture. This study applied descriptive-qualitative analysis in which the data were collected through observation, interview and literary study. There are several theories applied for this study including the functional theory and acculturation theory. The result of this study shows that bandung rangki has a very unique form and spatial arrangement. It only has one room without partition that consists of pedeman gede (bed for parents), pedeman kicak (bed for children), paon (kitchen), and pelangkiran (place to pray). The original pattern of the house’s arrangement is based on the concept of hulu-teben. However, along with the times there are changes in the materials used to build bandung rangki in which Pedawa people start to use materials like concrete, wall, root tile, and ceramics. This change is caused by the changes of the life style of the Pedawa’s people that start to prefer modern materials .